Editorial: Safeguarding the intellectual heritage of the humanity (Publicaciones en Ciencias y Tecnología, 2019)
Research is a process, that is, a sequence of steps in the search for knowledge, within the field of science and technology. This is responsible for raising questions, giving them answers and, finally, making the results public. For those who do, millions of men and women of the world, a career of vocation and dedication, in the search of updating knowledge and achieving the desired development of society. Why do they do it? It has different answers. Some of the answers have been raised in your search. This invites to navigate in turbulent waters, which demands skills, skills and qualities, such as perseverance and tenacity. It is hard work and, generally, with long-term results. But all the suffering vanishes before the emotion of a conclusive experiment, the completion of a project and a published article. At the end of the day it is worth it since you have gained a new knowledge. However, this process is a cycle and the researcher will always consider new projects and challenges.
Keywords: Editorial; Journal